2022
DOI: 10.3390/ijms23031313
|View full text |Cite
|
Sign up to set email alerts
|

Glutaredoxin Interacts with GR and AhpC to Enhance Low-Temperature Tolerance of Antarctic Psychrophile Psychrobacter sp. ANT206

Abstract: Glutaredoxin (Grx) is an important oxidoreductase to maintain the redox homoeostasis of cells. In our previous study, cold-adapted Grx from Psychrobacter sp. ANT206 (PsGrx) has been characterized. Here, we constructed an in-frame deletion mutant of psgrx (Δpsgrx). Mutant Δpsgrx was more sensitive to low temperature, demonstrating that psgrx was conducive to the growth of ANT206. Mutant Δpsgrx also had more malondialdehyde (MDA) and protein carbonylation content, suggesting that PsGrx could play a part in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The protein induced by cold stress, Rbm3, binds to the 60S ribosomal subunit, changes microRNA levels, and enhances overall protein synthesis [67]. In addition, studies have shown that CCT is a cold shock protein in Saccharomyces cerevisiae [68], and Glutaredoxin (Grx) interacts with GR and AhpC to enhance the low-temperature tolerance of the Antarctic psychrophilic bacterium ANT206 [69]. These results mean that these genes may play an important role in low-temperature stress and cold tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The protein induced by cold stress, Rbm3, binds to the 60S ribosomal subunit, changes microRNA levels, and enhances overall protein synthesis [67]. In addition, studies have shown that CCT is a cold shock protein in Saccharomyces cerevisiae [68], and Glutaredoxin (Grx) interacts with GR and AhpC to enhance the low-temperature tolerance of the Antarctic psychrophilic bacterium ANT206 [69]. These results mean that these genes may play an important role in low-temperature stress and cold tolerance.…”
Section: Discussionmentioning
confidence: 99%